A comparative evaluation of 0.25% bupivacaine and 0.25% levobupivacaine in peritubal infiltration in percutaneous nephrolithotomy - Devendra Singh; Neelima Tandon; Kushal Jethani; Tripathy, Anusha (Asian Journal of Medical Sciences, 2024)
Background: Percutaneous nephrolithotomy (PCNL) is a routine endourologic procedure in patients with renal calculi. Although it is less painful than open surgery, pain around the nephrostomy tube is a clinical problem; therefore, good post-operative analgesia is required to alleviate pain. Peritubal infiltration can be one of the choices to alleviate pain around the nephrostomy tube. Aims and Objectives: The aim of this study was to evaluate the efficacy of peritubal infiltration of local anesthetics for post-operative pain following PCNL. Materials and Methods: A total of 60 patients with American Society of Anesthesiologists Grade I/II scheduled for elective PCNL surgeries were randomly allocated into two groups. Group L received levobupivacaine 0.25% (30 mL) and Group B received bupivacaine 0.25% (30 mL). The duration of rescue analgesia, total dose of tramadol consumption in 24 h, hemodynamic parameters, and adverse events during the post-operative period were noted. Results: The mean duration of rescue analgesia in Group L was 274.50±24.89 min and in Group B was 275.33±23.04 min which was not significant (P>0.05). Conclusion: Peritubal infiltration of 0.25% levobupivacaine and 0.25% bupivacaine is efficient in alleviating post-operative pain after PCNL. Both drugs can be used for infiltration around nephrostomy tubes in PCNL surgeries safely and are associated with minimal side effects.